2024
DOI: 10.3390/foods13071127
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Correlates of Food Preference among Music Kinds

Yuanluo Jing,
Ziyuan Xu,
Yazhi Pang
et al.

Abstract: The calorie and taste choices of food have been shown to be related to the external environment, including music. Previous studies have mostly focused on manipulating basic auditory parameters, with few scholars exploring the impact of complex musical parameters on food selection. This study explored the effects of different kinds of music (classical, rock, jazz, and hip-hop) on food liking based on the calories (high and low) and taste (sweet and salty) using event-related potentials (ERPs). Twenty-four parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Event-related potential (ERP) studies have revealed that both early (N1 and N2) and late (P3) components are sensitive to the processing of food cues (Jing et al, 2024a). Early ERPs, such as occipital N1 occurring at 150-200 ms, have shown sensitivity to food type, re ecting early attention towards food stimuli (Meule et al, 2013;Schwab et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Event-related potential (ERP) studies have revealed that both early (N1 and N2) and late (P3) components are sensitive to the processing of food cues (Jing et al, 2024a). Early ERPs, such as occipital N1 occurring at 150-200 ms, have shown sensitivity to food type, re ecting early attention towards food stimuli (Meule et al, 2013;Schwab et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, one study indicated that inhibitory responses to high-calorie stimuli elicited larger N2 amplitudes, while inhibitory responses to low-calorie stimuli resulted in smaller N2 amplitudes (Carbine et al, 2017b). Research has demonstrated that N2 amplitudes were greater during exposure to rap music compared to jazz music (Jing et al, 2024a). A decrease in N2 response strength may indicate weakened inhibitory control (Y.…”
Section: Introductionmentioning
confidence: 99%